2006
DOI: 10.5194/acp-6-1389-2006
|View full text |Cite
|
Sign up to set email alerts
|

Relative humidity impact on aerosol parameters in a Paris suburban area

Abstract: Abstract. Measurements of relative humidity (RH) and aerosol parameters (scattering cross section, size distributions and chemical composition), performed in ambient atmospheric conditions, have been used to study the influence of relative humidity on aerosol properties. The data were acquired in a suburban area south of Paris, between 18 and 24 July 2000, in the framework of the "Etude et Simulation de la Qualité de l'air en Ile-de-France" (ESQUIF) program. According to the origin of the air masses arriving o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 80 publications
(111 reference statements)
7
59
0
Order By: Relevance
“…To better describe the variation of f (RH), a stepwise function is applied to fit the f (RH) measurements. On the basis of previously suggested empirical functions (Carrico et al, 1998(Carrico et al, , 2000(Carrico et al, , 2003Kotchenruther et al, 1999;Hegg et al, 2002;Randriamiarisoa et al, 2006;), a specific polynomial segment fitting, with the critical RH of 60 %, is applied in the parameterization of f (RH), as (the parameterization results are displayed in Table 2)…”
Section: A Parameterization Scheme Of F (Rh)mentioning
confidence: 99%
See 2 more Smart Citations
“…To better describe the variation of f (RH), a stepwise function is applied to fit the f (RH) measurements. On the basis of previously suggested empirical functions (Carrico et al, 1998(Carrico et al, , 2000(Carrico et al, , 2003Kotchenruther et al, 1999;Hegg et al, 2002;Randriamiarisoa et al, 2006;), a specific polynomial segment fitting, with the critical RH of 60 %, is applied in the parameterization of f (RH), as (the parameterization results are displayed in Table 2)…”
Section: A Parameterization Scheme Of F (Rh)mentioning
confidence: 99%
“…It is usually defined as the ratio of aerosol light scattering coefficients at a given RH (σ sc (RH)) and at dry condition (σ sc,dry ), namely f (RH) = σ sc (RH)/σ sc,dry . Numerous studies have demonstrated that the parameterized f (RH) can be generally expressed as an exponential function of RH (Covert et al, 1972;Fitzgerald et al, 1982;Carrico et al, 1998Carrico et al, , 2000Carrico et al, , 2003Kotchenruther et al, 1999;Hegg et al, 2002;Randriamiarisoa et al, 2006;Cheng et al, 2008;Fierz-Schmidhauser et al, 2010a, b, c;Zieger et al, 2010Zieger et al, , 2013. It should be noted that, different from the size-resolved aerosol diameter growth factor (g(RH)), f (RH) represents the overall aerosol light scattering enhancement factor of the aerosol population, and is jointly determined by the particle number size distribution (PNSD), chemical composition, density and refractive index.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both factors can be easily aquired, which makes the parameterization more practical. According to the relationship between K ex and aerosol volume concentration and the empirically exponential correlation between K ex and RH (Kasten, 1969;Carrico et al, 1998Carrico et al, , 2000Kotchenruther et al, 1999;Hegg et al, 2002;Randriamiarisoa et al, 2006;Eichler et al, 2008), the multiple regression scheme can be set up as follows:…”
Section: Parameterization Based On Two Factors Of Rh and Aerosol Volumentioning
confidence: 99%
“…Their assimilation in models leads to an improvement in weather forecasts (e.g., Collard and McNally, 2009;Bormann et al, 2010). Among the main components of the atmospheric state, water vapor is an essential element, which plays a key role in frontogenesis, convection (e.g., Held and Soden, 2000), cloud formation, and aerosol hydration (e.g., Larson and Taylor, 1983;Rood et al, 1987;Randriamiarisoa et al, 2006). In this way, it significantly influences the Earth climate and the atmospheric chemistry (e.g., IPCC, 2013).…”
Section: Introductionmentioning
confidence: 99%